Inmates in the Role of the "Wounded Healer": The Virtuous of Peer-to-Peer Programs in Prison - Elisha, Ety (International Journal of Criminology and Sociology, 2022)
Researchers in the field of crime desistance have recently focused on the strength-based role of the "wounded healer" or "professional-ex", as exemplified by former addicts and prisoners who desist from crime and recover through the professional practice of peer mentoring. Studies point to the many benefits inherent in the role of the “wounded healer” for incarcerated people employed in peer-based rehabilitation roles. These benefits can include opportunities to experience accomplishments and an increasing sense of ability and self-worth. Additional benefits include acquiring a new meaning and purpose in life, the development of a new self-identity, increasing feelings of belonging and satisfaction from life, and a stronger commitment to avoid crime. These findings suggest that formerly incarcerated individuals can form positive, pro-social relationships with their peers and serve as positive role models for them. The purpose of the present article is to review the current literature on peer-to-peer programs currently implemented in Western prisons, to establish and expand them, as a means of improving the rehabilitation efforts of present and past prisoners. It is recommended to examine the preservation of their benefits and effectiveness in the long run, both for aid providers and recipients.